Measurement of Sterigmatocystin Concentrations in Urine for Monitoring the Contamination of Cattle Feed - Yasuo Fushimi; Mitsuhiro Takagi; Seiichi Uno; Emiko Kokushi; Masayuki Nakamura; Hiroshi Hasunuma; Urara Shinya; Eisaburo Deguchi; Johanna Fink-Gremmels (Toxins, 2014)
This study aimed (1) at determining the levels of the fungal toxin sterigmatocystin (STC) in the feed and urine of cattle and (2) at evaluating the effects of supplementing the feed with a mycotoxin adsorbent (MA) on STC concentrations in urine. Two herds of female Japanese Black cattle were used in this study. The cattle in each herd were fed a standard ration containing rice straw from different sources and a standard concentrate; two groups of cattle from each herd (n = six per group) received the commercial MA, mixed with the concentrate or given as top-dressing, whereas a third group received no supplement and served as control. Urine and feed samples were collected at various time points throughout the experiment. STC concentrations were measured using liquid chromatography-tandem mass spectrometry (LC-TMS). STC concentrations in straw were higher in Herd 1 (range 0.15–0.24 mg/kg DM) than in Herd 2 (range <0.01–0.06 mg/kg DM). In Herd 1, STC concentrations in urine significantly declined 2 weeks after replacing the contaminated feed, whereas MA supplementation had no effect. In conclusion, mycotoxins in urine samples are useful biological markers for monitoring the systemic exposure of cattle to multiple mycotoxins, as well as evaluating the effectiveness of interventions.